ANALISA PEMILIHAN REFRIGERANT R22, R32 DAN R1270 PADA SISTEM REFRIGERATED SEA WATER (RSW) KAPAL PENANGKAP IKAN TRADISIOANAL - Prasetiyo Bayu Aji (LPPM Universitas Pekalongan, 2022)
Fish is a commodity that is not durable and easily damaged if placed in open space. Therefore, the fishermen use ice to cool the fish so that it can be kept fresh. However, this method is less effective and efficient because the ice melts quickly, so refrigeration technology is needed. The Refrigerated Sea Water (RSW) system is a technology for handling catch handling technology which is specially designed, installed as a place to accommodate fish/boat hatches so that the fish caught, especially certain types of fish, have economic value and can be maintained in quality. The process of cooling fish carried out by fishermen so far generally still uses traditional cooling methods, where the results of this cooling do not last long and are less efficient. The use of the Refrigerated Sea Water system as a cooling system on fishing vessels for small fishermen. Therefore, one alternative to the cooling system in traditional fishing boats is to use the Refrigerated Sea Water (RSW) system as a substitute for ice. In choosing a suitable refrigerant for the Refrigerated Sea Water (RSW) system on traditional fishing vessels, two parameters must be considered, namely the value (ODP, GWP), the selling price of refrigerant in the market and easy availability of refrigerant. The results of the analysis of several refrigerants R22, R32, R1270, refrigerant R32 are the most efficient refrigerants in the Refrigerated Sea Water system, because refrigerant R32 has no ODP and has a GWP value of 675 which is smaller than refrigerant R22 and greater than refrigerant R1270.